Combining iRGD with HuFOLactis enhances antitumor potency by facilitating immune cell infiltration and activation - Jie Shao; Kai Xin; Zhaoye Qian; Fangcen Liu; Lin Li; Junmeng Zhu; Qin Liu; Manman Tian; Baorui Liu (Human Vaccines & Immunotherapeutics)
Multiple research studies have demonstrated the efficacy of lactic acid bacteria in boosting both innate and adaptive immune responses. We have created a Lactococcus lactis variant that produces a modified combination protein with Fms-like tyrosine kinase 3 ligand and co-stimulator O × 40 ligand, known as HuFOLactis. The genetically modified variant was purposely created to activate T cells, NK cells, and DC cells in a laboratory setting. Furthermore, we explored the possibility of using the tumor-penetrating peptide iRGD to deliver HuFOLactis-activated immune cells to hard-to-reach tumor areas. Following brief stimulation with HuFOLactis, immune cell phenotypes and functions were assessed using flow cytometry. Confocal microscopy was employed to demonstrate the infiltrative and cytotoxic capabilities of iRGD-modified HuFOLactis-activated immune cells within tumor spheroids. The efficacy of iRGD modified HuFOLactis-activated immune cells against tumors was assessed in xenograft mouse models. HuFOLactis treatment resulted in notable immune cell activation, demonstrated by elevated levels of CD25, CD69, and CD137. Additionally, these activated immune cells showed heightened cytokine production and enhanced cytotoxicity against MKN45 cell lines. Incorporation of the iRGD modification facilitated the infiltration of HuFOLactis-activated immune cells into multicellular spheroids (MCSs). Additionally, immune cells activated by HuFOLactis and modified with iRGD, in combination with anti-PD-1 treatment, effectively halted tumor growth and prolonged survival in a mouse model of gastric cancer.